Dynamics of regional disparities in Slovakia in 2001 and 2011 - Michálek Anton; Podolák Peter; Madajová Michala Sládeková (Bulletin of Geography. Socio-Economic Series)
This paper is focused on the presentation of developmental tendencies of regional disparities in Slovakia in 2001 and 2011 from the point of view of selected and relevant socio-economic and demographic indicators. To test the divergence hypothesis of the regional disparities at a district level, these are evaluated by using multidimensional analysis of 14 indicators. The overall level and development of regional disparities are measured with the help of the methods of descriptive statistics and multi-criteria assessments (integrated index). The results confirm the hypothesis of divergence development as the basic tendency of regional development in Slovakia. The presented research has documented evident time shortening of significant changes in regions drifting towards divergent development. Rapid and, up to now, unprecedented changes (employment and wages growth, enterprise development, foreign investments increase, etc.), are evident and reflected in the majority of indicators – however, with different impacts on the regional level.